2021
DOI: 10.1111/1462-2920.15691
|View full text |Cite
|
Sign up to set email alerts
|

Global co‐occurrence of methanogenic archaea and methanotrophic bacteria in Microcystis aggregates

Abstract: Summary Global warming and eutrophication contribute to the worldwide increase in cyanobacterial blooms, and the level of cyanobacterial biomass is strongly associated with rises in methane emissions from surface lake waters. Hence, methane‐metabolizing microorganisms may be important for modulating carbon flow in cyanobacterial blooms. Here, we surveyed methanogenic and methanotrophic communities associated with floating Microcystis aggregates in 10 lakes spanning four continents, through sequencing of 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 119 publications
1
16
0
Order By: Relevance
“…2b ). Following earlier work 8 , 28 , 16S rRNA and mcrA sequences were affiliated with the Methanosaeta and Methanospirillum genera, indicating the potential for hydrogenotrophic and acetoclastic (but not methylotrophic) methanogenesis 28 . (Incubations were also monitored to confirm that they were under oxic conditions at all times; Table S1 .)…”
Section: Resultssupporting
confidence: 64%
“…2b ). Following earlier work 8 , 28 , 16S rRNA and mcrA sequences were affiliated with the Methanosaeta and Methanospirillum genera, indicating the potential for hydrogenotrophic and acetoclastic (but not methylotrophic) methanogenesis 28 . (Incubations were also monitored to confirm that they were under oxic conditions at all times; Table S1 .)…”
Section: Resultssupporting
confidence: 64%
“…In fact, in our study, 88% of the archaeal methanogens (Methanobacteriales, Methanomicrobiales, Methanosarcinales, and Methanomassiliicoccales) did not correlate to the Methylacidiphilaceae. This points to a possible interaction between Synechococcus and Methylacidiphilaceae, as methanogen and methanotroph, demonstrated in the Microcystis phycosphere . Nevertheless, the potential involvement between Methylacidiphilaceae and cyanobacteria in the oxic methane cycle is still a subject of further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Reports on Microscillacaea are limited, and their ecological role is unclear. Yet, all the available studies have related this microbe group to Microcystis aggregates, implying that the heterotrophs possess unique functional potential linked to the proliferation of Microcystis . A study on methane oxidation activity within Microcystis blooms has shown enriched Microscillacaea in lakes when methane-oxidizing bacteria (MOB) increased .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the Methylocystis-type sequences we obtained from cyanobacterial isolates (Supplementary Table 4) match this idea of oligotrophic strains being able to survive in the cyanosphere. Additionally, other methanotrophs may be able to survive in the cyanosphere under natural conditions, where large amounts of methane may be formed during cyanobacterial blooms (Li et al, 2021). Another option for supporting MOB growth and activity may be hydrogen gas that is generated during nitrogen fixation by cyanobacteria (Lopes Pinto et al, 2002;Dutta et al, 2005).…”
Section: Cyanobacteria-methane-oxidizing Bacteria Associationsmentioning
confidence: 99%
“…We tested this hypothesis under laboratory conditions, first testing the possibility of cyanobacteria growth in the presence of methane and methanotrophic bacteria without external input of CO 2 , and second, testing the 13 C transfer from CH 4 to cyanobacteria. Since we had no access to axenic cultures of cyanobacteria and there are known examples of methanogens and MOB associations with phytoplankton (Grossart et al, 2011;Mulhollem et al, 2016;Samad et al, 2020;Li et al, 2021), we decided to test the possibility of carbon transfer via MOB metabolites utilized by other organisms that later release CO 2 or organic substances. We also tested the influence of light conditions on the overall performance of the consortium.…”
Section: Introductionmentioning
confidence: 99%